Hybrid Energy Storage Control Method for Wave Energy Power Supply System in Comprehensive Observation Buoys - Xu LIU; Zhen CHEN; Zhen LIU; Ming LI (水下无人系统学报)
Wave energy is a widely distributed green renewable energy source capable of providing continuous electrical power to comprehensive observation buoys. However, its rapid fluctuations and high peak-to-average ratio require hybrid energy storage systems to smooth out its energy fluctuations for a reliable electrical load supply. These hybrid energy storage systems need to balance power and energy density characteristics, and energy management strategies are important for fully utilizing the characteristics of different devices and extending the system’s lifespan. This paper focused on energy distribution and power control methods of energy storage systems in wave energy supply and proposed a power distribution and control strategy for hybrid energy storage system based on deep deterministic policy gradient(DDPG), so as to maintain bus stability and leverage the advantages of two energy storage technologies of batteries and supercapacitors. Simulation and physical experiments demonstrate that this strategy greatly reduces peak battery charge/discharge power, keeps bus voltage ripple below 1.6%, and significantly enhances the stability of the wave energy power supply system.